Shared Heritage Diplomacy of Indonesia and Malaysia as Soft Power in The Southeast Asia Region - Shella Hajura (Jurnal Hubungan Internasional, 2022)
The decision of the Governments of Indonesia and Malaysia to collaborate on shared cultural heritage is an interesting phenomenon. The dispute over cultural heritage claims between the two countries several years ago strained their relationship. The reluctance of both governments to understand each other’s different views and take unilateral action regarding their shared cultural heritage has complicated the cultural conflicts. In 2017, Indonesia and Malaysia collaborated to register pantun as shared cultural heritage in the UNESCO. Three years later, UNESCO designated pantun as the world’s intangible cultural heritage from Indonesia and Malaysia. This research aims to analyze the motivation of the cooperation between Indonesia-Malaysia in promoting shared cultural heritage at the international level, with a case study of the registering pantun as a representative list of UNESCO, carried out in 2017-2020. This study employed the concept of heritage diplomacy and soft power with a qualitative analysis method. The findings disclosed that the motivation of the Governments of Indonesia and Malaysia was to fulfill their political interest at the bilateral, regional and international levels. Using cultural heritage as diplomacy demonstrates that culture can solve the political problems between states and become their soft power.